Morphonological transformations of derivational nests with the top adjectives ending -r(yi) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with the analysis of the adjectival derivatives of the point of view of morphonology. A central issue is in formal grammatical description of top adjectives. This paper focused on the morpheme structure of the motivation stems and the derivational suffixes. The data indicate the structure the contact zone, morphonological positions and the main modifications within the analysed word building nests.
Keywords: morphonological transformations; word building nest; alternation